Sustainable nanosystems development, properties, and applications - Putz, Mihai V.; Mirica, Marius Constantin (Advances in chemical and materials engineering (ACME), 2017)
This book features emergent research and theoretical concepts in the areas of nanotechnology, photovoltaics, electrochemistry, and materials science, as well as within the physical and environmental sciences.